2009
DOI: 10.3340/jkns.2009.45.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Dural Arteriovenous Fistula with Supply from the Lateral Sacral Artery-Case Report and Review of Literature-

Abstract: The authors report a case of spinal dural arteriovenous fistula (SDAVF) that is supplied by a lateral sacral artery. A 73-year-old male presented with gait disturbance that had developed 3 years ago. Spinal magnetic resonance imaging suggested a possible SDAVF. Selective spinal angiography including the vertebral arteries and pelvic vessels showed the SDAVF fed by left lateral sacral artery. The patient was subsequently treated with glue embolization. Three days after the embolization procedure, his gait distu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Most patients show some degree of dysfunction as demonstrated by progressive paraparesis, lower extremity sensory abnormality, and bowel and bladder dysfunction [1,2,3,5,6]. Despite the variable presentation of myelopathy and neurologic dysfunction in SDAVF, our patients reported progressive bilateral lower extremity weakness, pain, gait disturbance, and bowel and bladder incontinence, similar to cited cases of SDAVF [2,3,6].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Most patients show some degree of dysfunction as demonstrated by progressive paraparesis, lower extremity sensory abnormality, and bowel and bladder dysfunction [1,2,3,5,6]. Despite the variable presentation of myelopathy and neurologic dysfunction in SDAVF, our patients reported progressive bilateral lower extremity weakness, pain, gait disturbance, and bowel and bladder incontinence, similar to cited cases of SDAVF [2,3,6].…”
Section: Discussionmentioning
confidence: 60%
“…In 2007, Nishio et al [4] compiled 42 cases of SDAVFs arising from internal iliac arteries, including their case. However, some authors believe the actual incidence is much higher than reported in the literature, due to “negative” spinal angiograms and nonspecific clinical presentations of myelopathy attributed to other disorders [5,6]. Nishio et al [4] recommended that an angiographic examination of the internal iliac arteries be performed in patients with suspected SDAVF when the lesion has not been identified in the thoracic or lumbar region.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although rare, they account for approximately 80% of all spinal vascular abnormalities. [1] Vascular malformations of the gastrointestinal tract are also rare in children. [2] Concurrent spinal dural AVF and cecal AVM have not been reported till now.…”
Section: Introductionmentioning
confidence: 99%